التطبيع مع العدو الإسرائيلي: حكمه وأثره على الواقع الاسلامي - العماد، هدى علي يحيى Alemad, Huda Ali Yahia (جامعة الناصر, 2021)
يعد الصراع المعاصر بين المسلمين واليهود من أعظم ما مرت به الأمة المسلمة من المحن في تاريخها الطويل حيث جاء هذا الصراع والأمة المسلمة تعيش ضعفا وتفرقا لم يسبق لهما مثيل في تاريخها، فنحن في زمن تطاولت عليه القوى الشيطانية على أمة الإسلام والمسلمين وتمكنت قوى الاستكبار من فرض هيمنتها على الدول الإسلامية وما نلاحظه اليوم من تعاون لقوى الشر لتطبيع الشعوب العربية المسلمة، ليعتبروه من منطلق التطور والتقدم وهو في الحقيقة الفساد والانحراف عن التعاليم الإسلامية السمحة، واليهود بالتطبيع سينعمون بقوة وهيمنة عالمية لم يسبق لهم أن نعموا بمثلها، ولا بد من أن نعي يقينا أن مبدأ المولاة والمعادة أصلا من أصول الدين، وأمرا تعبديا، وتطبيقه والالتزام به فيه عزة وكرامة لهذه الأمة، هذا ومن الغرابة أن العداء استمر بين اليهود والعرب قرابة خمسين عاما ولم يكن أحد من المسلمين يجرؤ على التفكير في الصلح مع اليهود فضلا عن إبرامه والتوقيع عليه والتسابق إليه، ولأهمية الموضوع وتفصيلاته أقتضى إلى تقسيمه إلى: تمهيد وخمسة فصول وذلك على النحو التالي التمهيد: أهمية البحث عن التطبيع في الوقت المعاصر، تاريخ التطبيع ومراحله، الأسباب أدت إلى هذا التغير المفاجئ والتسارع إلى تقبيل بني صهيون وانتظار النجاة على أيديهم من جميع المشكلات، الموقف اليمني المناهض للتطبيع مع العدو الإسرائيلي. الفصل الأول: التعاريف والمصطلحات. الفصل الثاني: الحكم الشرعي للصلح -أقسامه وشروط صحة الصلح بين المسلمين والكفار، حكم التطبيع مع اليهود، -مناقشة أدلة من أجاز التطبيع العصري بناء على صلح الحديبية ونحوه، وحكم العمل في المستوطنات، وحكم التعامل مع الكفار بيعا وشراء وشركة وإجارة ونحوه، ومدى دخول كل ذلك في عقيدة الولاء والبراء. الفصل الثالث: الأهداف والمجالات والوسائل والتجليات والأشكال والأنشطة والمظاهر التي ينطبق عليها التطبيع، وشروط الواقع الراهن لقيام سياسية التطبيع. الفصل الرابع: آثار ومخاطر التطبيع على الواقع الإسلامي، وآثار التطبيع على القضية الفلسطينية والشعب الفلسطيني، الدور الأمريكي في التطبيع، السعي اليهودي لتمييع الإسلام في المجالات المختلفة، البعد العربي والدولي والإسرائيلي على التطبيع. الفصل الخامس: الأمل في وعي الأمة الإسلامية، ودور المسلم في خدمة دينه، طرق مواجهة التطبيع، الدور العربي في مناهضة التطبيع، وتوضيح دور الجامعات والمراكز البحثية في مناهضة التطبيع مع الكيان. The recent Muslim-Jewish conflict is one of the most distressing events the Muslim nation has experienced throughout history. This conflict came while the Muslim nation undergoes an unprecedented weakness and division. Today, evil forces have trampled on the Islamic nation, and the powers of arrogance have been able to impose their hegemony on Islamic countries. These forces collaborate to normalize the Arab and Muslim relations with the Israelis, considering this a form of development and progress; whereas in fact it is corruption and deviation from the tolerant Islamic teachings. By normalization, the Jews will have global dominance that they have never enjoyed before. For the pride and dignity of this nation, the principle of loyalty and enmity, as one of the religious fundamentals that should be applied and adhered to. During the fifty-year period of Arab-Israeli conflict, none of the Muslims dared to establish peace with the Jews, let alone concluding, signing and racing towards normalization. This significant study is divided into a preface and five chapters, as follows. The preface presents the significance of working on normalization today, the history of normalization and its stages, the reasons that led to this sudden change and the acceleration to appreciate the Zionists and awaiting their solutions to all problems, and finally the attitude of Yemenis towards normalization with the Israeli enemy. Chapter One presents the definition of the study terms and concepts. Chapter Two discusses the legal rulings on reconciliation, its types and conditions for the validity of reconciliation between Muslims and infidels, and on normalization with the Jews. It also discusses evidence that permitted modern normalization based on the Treaty of Hodaybiah and the ruling on working in settlements, conducting business deals with infidels in light of the doctrine of loyalty and enmity. Chapter Three presents the objectives, areas, means, manifestations, forms and activities to which normalization applies, and the conditions for establishing normalization policy within the current reality. Chapter Four discusses the impacts of normalization on the Islamic reality, and on the Palestinian issue. It also exposes the US role in normalization, the Jewish endeavor to dilute Islam in various fields, as well as the Arab, international and Israeli perception of normalization. Chapter Five concludes with emphasis on the role of Muslims and Arabs in serving their religion by adopting anti-normalization attitudes. It also highlights the role of universities and research centers in combating normalization with the Zionist entity.
Keywords: الإحتلال الصهيوني -- تاريخ التطبيع -- القضية الفلسطينية -- الواقع الاسلامي -- حركات المقاومة